NUDT15 Polymorphism Confer Increased Susceptibility to Thiopurine-Induced Leukopenia in Patients With Autoimmune Hepatitis and Related Cirrhosis - Fan, Xiaoli; Yin, Dandan; Men, Ruoting; Xu, Heng; Yang, Li (Frontiers in Pharmacology, 2019)
The aim of this study was to investigate the influence of NUDT15 R139C and thiopurine S-methyltransferase (TPMT) on azathioprine (AZA) induced leukopenia in in patients with autoimmune hepatitis and related cirrhosis. A total of 149 Chinese AIH patients with a history of azathioprine treatment were retrospectively evaluated. The clinical and epidemiological characteristics of the patients were obtained from an electronic database and reviewed. NUDT15 (rs116855232) and TPMT∗3C (rs1142345) SNPs were genotyped using a real-time PCR method. 12 patients developed leukopenia, and this adverse drug reaction was significantly associated with the T risk allele in NUDT15 (P < 0.00001, odds ratio = 20.41; 95% confidence interval (7.84, 53.13)), with the sensitivity and specificity of 91.67% and 89.05%, respectively. The median maintenance dosages for patients with the rs116855232 CC and CT genotypes were 1.23 (0.95, 1.53) mg.kg-1.d-1 and 0.96 (0.83, 1.19) mg.kg-1.d-1, respectively (P = 0.028). In contrast, no significant association was observed for TPMT∗3C genotypes. Notably, subgroup analysis of the 13 patients with leukopenia before therapy (12/13 of these patients were NUDT15 wild-type homozygotes), these white blood cell counts did not show further reduction after azathioprine treatment and maintenance dosage was 1.13 (0.94, 1.60) mg.kg-1.d-1. Therefore, NUDT15 polymorphisms are significantly associated with thiopurine-induced leukopenia in Chinese patients with AIH and related cirrhosis, and adjusting the azathioprine dosage should be considered in patients according to the NUDT15 R139C genotypes.